Mining Educational Data To Analyze The Performance Of Infrastructure Facilities Of Gujarat State (International Journal of Engineering and Computer Science, 2017)
School plays major role in our society of Economics, Education and Environment. A  School infrastructure represents good School. Good school infrastructure includes with building in good shape including an adequate number of well-organized classrooms, sufficient blackboards, access to adequate clean drinking water, common toilets, girl’s toilets etc. The School which has got sophisticated and produces the good result then it’s attracted many students. The schools were analyzed with reference to staff, infrastructure, amenities and achievements. The data was analyzed by using WEKA software. Educational officers to take appropriate steps to improve the quality of education in Gujarat State. An attempt has been made for broad mapping and analysis of existing infrastructures in the context of planning scheme in Gujarat State district wise, and to delineate the development zones of educational infrastructure facilities. The thematic layers considered in this study are infrastructure accessibility, type and condition of classroom and number of classroom allocated for the educational system at primary and upper primary level. Data mining has emerged as one of the major research domain in the recent decades in order to extract implicit and useful knowledge. Data Mining is an emerging technique with the help of this one can efficiently learn with historical data and use that knowledge for predicting future behavior of concern areas. The work aims to use data mining techniques which mines required information, so that the present education system may adopt this as a strategic management tool.